1976
DOI: 10.1115/1.3452798
|View full text |Cite
|
Sign up to set email alerts
|

Two-Fluid Flow Between Rotating Annular Disks

Abstract: The general hydrodynamic behavior at small clearance Reynolds numbers of two fluids of different density and viscosity occupying the finite annular space between a rotating and stationary disk is explored using a simplified version of the Navier-Stokes equations which retains only the centrifugal force portion of the inertia terms. A criterion for selecting the annular flow fields that are compatible with physical reservoirs is established and then used to determine the conditions under which two-fluid flows i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The study conducted by Yuan et al [14] showed that the oil film, once ruptured, is swept away by the faster of the two rotating annular surfaces over a cavity of air that extends to the conjunctional external radius. This is supported by the analysis of Zweig and Sneck [15]. Additionally, Yuan et al [14] showed that the rotational speed of both surfaces is critical in determining the position of lubricant film rupture.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The study conducted by Yuan et al [14] showed that the oil film, once ruptured, is swept away by the faster of the two rotating annular surfaces over a cavity of air that extends to the conjunctional external radius. This is supported by the analysis of Zweig and Sneck [15]. Additionally, Yuan et al [14] showed that the rotational speed of both surfaces is critical in determining the position of lubricant film rupture.…”
Section: Introductionmentioning
confidence: 83%
“…Integrating equation (13) with respect to the radius yields equations (14) and (15), where equation (15) describes the pressure at any radial location in the lubricant film:…”
Section: Analytical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…They also discussed the uniform suction effects through the rotating disk. Hydrodynamic behavior of two fluids at low Reynolds number, both having different density and viscosity between a rotating and a stationary disk was explored by Zweig et al [7]. Qayyum et al [8] discussed the problem of non-steady axisymmetric Jeffrey fluid flow between two parallel disks.…”
Section: Introductionmentioning
confidence: 99%
“…Observation of lubricant film rupture in rotary components, separated by a thin lubricant film shows a single free boundary is often formed, with the remaining volume of lubricant swept away by the rotating surface. Examples of this are reported for wet clutches [8,13,14], as well as for rotary face seals [15,16]. This indicates that wet brakes and clutch packs should use a separation (Prandtl-Hopkins incipient reverse flow) boundary conditions rather than the commonly employed cavitation boundary conditions.…”
Section: Introductionmentioning
confidence: 99%